(untitled) (Journal of Academic Research, 2019)
Background: Raw (fresh) vegetables as part of a healthy diet is an important key to help boost immune health. However, they could also have a negative impact on humans. Vegetables, especially those that are consumed raw and not properly washed, have been the major way for the transmission of human pathogens. For example, Cryptosporidium and Giardia infection may be acquired in different ways including by consumption of contaminated vegetables and water. The purpose of this paper is to describe the detection of Giardia cyst and Cryptosporidium oocyst contamination in some common salad vegetables sold at the small retail and local markets in Kufra city, Libya. Methods: A total of 250 samples including five different types of fresh salad vegetables were randomly collected and examined between July 2013 and February 2014, for the prevalence of both parasites by using local accepted standard method, similar to USEPA Method 1623, followed by concentration of target organisms from other particulates by IMS then completed by IFA and microscopy as specified by Method 1623.